Priesthood in the Tradition of the St. Thomas Christians of India - Kalayil, Thomas (Asian Horizons, 2009)
According to the strong tradition and belief of the St.Thomas Christians of India, it was St.Thomas, the Apostle of Christ, who preached the Gospel to their forefathers and baptized them.1 The favourite term by which they designated themselves even from early centuries was Nazrani. This term meant the follower of the Nazarene Jesus. This is an analogue for the designation Christian.That the St.Thomas Nazrani community had Priests and Bishops ordained by St.Thomas himself is also a strong tradition among them.2 It is but logical to think that St.Thomas ordained Bishops and Priests as the other Apostles did in the Churches founded by them.